Using computer animation for emergency medicine education. (2017) - Zheng, Huilong; Adamo-Villani, Nicoletta; McGraw, Tim; Griggs, Rosanne
An experiment was conducted to investigate the effectiveness of animation for emergency medicine education. Two groups of participants were assessed on their ability to respond to three medical emergency situations in simulated test scenarios. The control group received instruction in traditional lecture/demo format, whereas the experimental group received instruction from a computer animation. Participants' knowledge of the medical emergencies response procedures was assessed according to speed and accuracy of the treatment, and ability to complete every step and execute the steps in the correct order. Results revealed no statistically significant difference in procedural knowledge between the control and experimental groups.